Physiological properties of the lamina I spinoparabrachial neurons in the mouse. (28th February 2019) - Allard, Julien
Abstract : Key points: Spinal cord lamina I neurons receiving dense input from nociceptors and projecting to the parabrachial area at the ponto‐mesencephalic junction form the major ascending pain‐related pathway in rodents. Lamina I spinoparabrachial (SPB) neurons have never been characterized in mice, despite the growing and extensive use of this species to understand the contribution of lamina I SPB neurons in chronic pain. The electrophysiological properties of lamina I SPB neurons recorded here in anaesthetized mice are comparable to those of rat or cat, forming a nociceptive and thermoreceptive pathway. It was confirmed 'on line' that lamina I SPB neurons that normally encode noxious stimuli can receive input from low threshold mechanoreceptors in certain conditions. The present work indicates that the study of lamina I SPB neurons in vivo could take advantage of the use of genetically modified mice. Abstract: Ongoing studies investigating the role of lamina I projection neurons in the generation of chronic pain are mainly based on the use of genetically modified mice. However, lamina I projection neurons have never been physiologically characterized in this species. The present work aimed to fill this gap, and to assess the effect of spinal 'disinhibition' that may occur in chronic pain states on the responses of these neurons to light touch. Seventy lamina I spinoparabrachial (SPB) neurons were characterized in anaesthetized mice. These neurons showed low central conduction velocities (<12.4 m s −1 ) and wide range of responses. Fifty‐six neurons responded equally to noxious mechanical and thermal (heat) stimuli (16% responded consistently to light touch). Modality‐specific neurons responded preferentially to thermal (cold) stimuli ( n = 10) and pinch ( n = 2), or specifically to heat ( n = 2). Spinal bicuculline and strychnine application induced responses to brush in half of the neurons tested, confirming directly the potential connection between low threshold mechanoreceptors and nociceptive‐specific neurons, responsible for mechanical allodynia. Remarkably, the effect of the treatment was highly variable and apparently independent of the initial profile of the neurons. The present data confirm that mice lamina I SPB neurons have the expected characteristics to form a nociceptive and thermoreceptive pathway, but they constitute a highly heterogeneous group. The differential effect of spinal disinhibition observed here suggests that a subgroup of lamina I SPB neurons might be responsible for abnormal pain in pathological conditions, and emphasizes the importance of in vivo recording, a neglected approach. Key points: Spinal cord lamina I neurons receiving dense input from nociceptors and projecting to the parabrachial area at the ponto‐mesencephalic junction form the major ascending pain‐related pathway in rodents. Lamina I spinoparabrachial (SPB) neurons have never been characterized in mice, despite the growing and extensive use of this species to understand the contribution of lamina I SPB neurons in chronic pain. The electrophysiological properties of lamina I SPB neurons recorded here in anaesthetized mice are comparable to those of rat or cat, forming a nociceptive and thermoreceptive pathway. It was confirmed 'on line' that lamina I SPB neurons that normally encode noxious stimuli can receive input from low threshold mechanoreceptors in certain conditions. The present work indicates that the study of lamina I SPB neurons in vivo could take advantage of the use of genetically modified mice.